Pain reduction by dehydrated human amnion/chorion membrane allograft in nondiabetic leg ulcers might be an early indicator of good response: A case series. Issue 4 (5th June 2020) - Mueller, Simon M.; Navarini, Alexander A.; Itin, Peter; Schwegler, Simon; Laeuchli, Severin; Goldust, Mohamad; Ivanova, Katja
Abstract: Dehydrated human amnion/chorion membrane allograft (dHACM) derived from placenta is increasingly used for skin and soft tissue repair in several medical specialties. Promising effects of dHACM were also reported in chronic venous and diabetic leg ulcers. However, dHACM is cost‐intensive and its effect on chronic leg ulcers of other etiologies and pain reduction is unknown. Clinical predictors of a favorable response to dHACM during the early treatment period could help to limit unnecessary costs. In our case series with six patients suffering from chronic lower leg ulcers of various etiology, the effect of dHACM once per week on reduction of pain and wound size during a 5‐week period was examined. dHACM resulted in effective pain reduction and improved wound healing in three patients with chronic leg ulcers due to calciphylaxis, chronic venous disease and reactive angioendotheliomatosis. Pain reduction after 1 to 2 applications of dHACM predicted a favorable healing response. Hence, our observation indicates that assessment of pain 3 weeks after initiation of dHACM may be a clinical predictor to justify dis‐/continuation of dHACM and thereby may help to limit costs.